The Influence of Knowledge Management and Organization Innovativeness on The Organizational Resilience: A Theoretical Framework - Annisa Dewi Akbari; Didien Suhardini; Agung Sasongko (OPSI, 2022)
Covid-19 pandemic had a real negative impact on all sectors, including startup. More than half of total start-ups in Indonesia can’t survive the crisis caused by Covid-19 pandemic. This requires the organization to be able to develop its ability to survive. The answer to this challenge is organization resilience. Organizational resilience can anticipate potential threats, respond to unexpected events, and achieve sustainable growth. Through a recent literature study related to theory and conceptualization of organizational resilience, as well as considering contextual factors adapted to organizations, especially startup, this research succeeded in developing a theoretical model related to organizational resilience. The framework is built on three variables, namely organization resilience as the dependent variable, knowledge management as independent variable, and organization innovativeness as intervening variable, with 11 sub-variables, and four hypotheses. Furthermore, this framework can be an initial picture and insight for Chief Executive Officers (CEOs) of startup, to navigate organizations in dynamic environments, crisis situations, or in the midst of today's global competition